Linux administration a beginners guide - Soyinka, Wale (New York, NY McGraw-Hill Osborne Media, 2012)
"Deploy and manage a Linux server quickly and easilyThoroughly revised to cover the most current Linux distributions and the latest Linux kernel release, Linux Administration: A Beginner's Guide, Sixth Edition shows new and inexperienced Linux system administrators how to set up and configure Linux. The sixth edition adds key updates about the latest Linux distributions and focuses on Fedora, openSUSE, and Ubuntu. The book adds coverage of newer technologies, including virtualization, infrastructure services, Windows and Linux integration, Linux routers and firewalls, LDAP, printing, and new hardware now supported by the updated Linux kernel.This trusted, bestselling beginner's guide continues its recipe and step-by-step approach to Linux system administration, including managing files and software, users and user rights, basic security, Internet and intranet services, and kernel customization. The book makes it easy for existing system administrators to quickly zero in on relevant sections of the book to solve or tackle real-world Linux administration issues.Linux Administration: A Beginner's Guide, Sixth Edition Covers the major distributions of Linux server for Fedora, openSUSE and Ubuntu, and the latest Linux kernel release Includes new chapters introducing Distributed File Systems--key for today's cloud computing/virtualization-centric world Contains a new chapter on the business case for Linux and the marketability of Linux administration skills Step-by-step coverage: Technical Summary of Linux Distributions and Windows Server 2008; Installing Linux in a Server Configuration; Installing Software; Single Host Administration; Managing Users; The Command Line; Booting and Shutting Down; File Systems; Core System Services; Compiling the Linux Kernel; Knobs and Dials: The /proc File System; Security and Networking; TCP/IP for System Administrators; Network Configuration; Configuring the Linux Firewall and Router; Local Security; Network Security; Configuring Internet Services; DNS; FTP; Web Servers; SMTP; POP and IMAP; SSH and Encryption; Virtualization; Configuring Intranet Services; Network File Systems (NFS); Distributed File Systems; Network Information Service (NIS); LDAP; Samba (SMB/CIFS); Printing; DHCP; Backups "--
"Effectively deploy and maintain Linux and other Free and Open Source Software (FOSS) on your servers or entire network using this practical resource. Linux Administration: A Beginner's Guide, Sixth Edition provides up-to-date details on the latest Linux distributions, including Fedora, Red Hat Enterprise Linux, CentOS, Debian, and Ubuntu. Learn how to install and customize Linux, work from the GUI or command line, configure Internet and intranet services, interoperate with Windows systems, and create reliable backups. Performance tuning, security, and virtualization are also covered and real-world examples help you put the techniques presented into practice"--
Machine generated contents note: Part 1: Linux Administration Essentials -- Ch 1: Technical Summary of Linux Distributions and Windows Server 2008 -- Ch 2: Installing Linux in a Server Configuration -- Ch 3: Installing Software -- Part 2: Single Host Administration -- Ch 4: Managing Users -- Ch 5: The Command Line -- Ch 6: Booting and Shutting Down -- Ch 7: File Systems -- Ch 8: Core System Services -- Ch 9: Compiling the Linux Kernel -- Ch 10: Knobs and Dials: The /proc File System -- Part 3: Security and Networking -- Ch 11: TCP/IP for System Administrators -- Ch 12: Network Configuration -- Ch 13: Configuring the Linux Firewall and Router -- Ch 14: Local Security -- Ch 15: Network Security -- Part 4: Configuring Internet Services -- Ch 16: DNS -- Ch 17: FTP -- Ch 18: Web Servers -- Ch 19: SMTP -- Ch 20: POP and IMAP -- Ch 21: SSH and Encryption -- Ch 22: Virtualization -- Part 5: Configuring Intranet Services -- Ch 23: Network File Systems (NFS) -- Ch 24: Distributed File Systems -- Ch 25: Network Information Service (NIS) -- Ch 26: LDAP -- Ch 27: Samba (SMB/CIFS) -- Ch 28: Printing -- Ch 29: DHCP -- Ch 30: Backups
1
Keywords: Linux; COMPUTERS / System Administration / Linux & UNIX Administration; Operating systems (Computers)